Knit to be tied [large type] - Sefton, Maggie (Sefton, Maggie. Knitting mystery, 2016)
In Fort Connor, Colorado, the friends at the House of Lambspun knitting shop are welcoming a new face into the fold. Shy, sweet, and pregnant Nancy Marsted would like to knit a baby hat, and the Lambspun ladies are happy to show her the ropes. Sharing their own pregnancy yarns, they soon learn that the baby's father isn't the man Nancy dreamed he was. Then one dark night a speeding car mows down the dad to be and strikes a cyclist. Worried that a crazed killer is on the loose, the knitters put down their needles and cut to the chase.